Financial Performance of Telecommunication Sector Companies Before And During The Covid-19 Pandemic - Alifa Jauzaa; Heni Hirawati (Universitas Airlangga, 2021)
This research aims to analyze the financial performance of telecommunications sektor companies judging from profitability ratios which unclude ROA, ROE, and NPM period before and during the Covid-19 pandemi. Covid-19 has an impact on the weakening of various sektors of the economy. Nevertheless, there are still some sektors that are able togrow. One of them is the telecommunications sektor. The internet plays a big role in community activities that are generally carried out online, causing an increase in the performance of telecommuniciation issuers. The data used in this study is the financial statements of telecommunication companies listed on the Indonesia Stock Exchange quarter 2 of 2019-quarter 1 of 2021 and analyzed using descriptive methods. The results showed that the financial performance of telecommunications sektor companies was guided by the average value of profitability ratios that include ROA, ROE, and NPM obtained results that during the covid-19 pandemi were first confirmed, overall, the average financial performance of telecommunications sektor companies has increased. Assesment with the analysis of Hotteling’s T2 test also provided results that there was no difference in financial performance in terms of the profitability ratio between before and during the covid-19 pandemi